2013
DOI: 10.1002/cncr.28340
|View full text |Cite
|
Sign up to set email alerts
|

Treatment trade‐offs in myeloma: A survey of consecutive patients about contemporary maintenance strategies

Abstract: BACKGROUND Two randomized trials have demonstrated improved progression free survival (PFS) with lenalidomide maintenance following autologous transplantation for multiple myeloma (MM). Overall survival (OS) results are conflicting and quality of life (QOL) data is lacking. We conducted a systematic survey of MM patients regarding what constitutes a meaningful benefit that would make burdens of maintenance treatments (toxicity and cost) acceptable. METHODS We mailed a self-administered survey to 1159 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…[ 27 ] When myeloma patients were surveyed on their opinion on maintenance treatment, development of peripheral neuropathy was the most common worrisome potential toxicity, identified by 27% of patients. [ 29 ] Our study suggests that use of SC weekly induction may overcome this barrier for many patients and allow maintenance at reduced frequency with likely further reduced neuropathy risk. SC administration also eliminates the need for IV access, reduces infusion chair times, cost and is preferred by patients.…”
Section: Discussionmentioning
confidence: 97%
“…[ 27 ] When myeloma patients were surveyed on their opinion on maintenance treatment, development of peripheral neuropathy was the most common worrisome potential toxicity, identified by 27% of patients. [ 29 ] Our study suggests that use of SC weekly induction may overcome this barrier for many patients and allow maintenance at reduced frequency with likely further reduced neuropathy risk. SC administration also eliminates the need for IV access, reduces infusion chair times, cost and is preferred by patients.…”
Section: Discussionmentioning
confidence: 97%
“…Although HRQoL showed an initial decline during active treatment, which could be partly attributed to treatment‐related toxicity, limited post‐treatment data (not shown) suggest that patients’ HRQoL post‐treatment was similar to baseline levels; however, conclusions cannot be reached due to minimal data. Whether the impact of side effects, such as neurotoxicity (which ranks among the most worrisome toxicities for patients with MM [Burnette et al , ]), is offset by improvements in disease‐related symptoms and prolonged progression‐free and overall survival requires further studies with prolonged patient follow‐up over a period of several years. Additionally, accumulating evidence also points toward the ability to improve on the tolerability of established combination regimens for MM, such as by extending the dosing interval for BTZ to once‐weekly administration (Bringhen et al , ; Girnius et al , ; Totani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, patients' preferences are integrated into clinical decision making in those countries where maintenance treatment is supported by the national health care system. A recent survey on the willingness of patients to accept toxicities in return for gain in outcome showed that the willingness among patients to receive maintenance was substantially influenced by the expected toxicity and survival gain [44]. In case of PFS but no OS benefit, only 23% of patients would choose maintenance if it was associated with moderate toxicity, but the proportion would rise to 92% in case of only mild side effects.…”
Section: Treatment Strategies In 2014: European Perspectivementioning
confidence: 99%